PENGARUH PEMANFAATAN PERPUSTAKAAN SEKOLAH TERHADAP KETERAMPILAN MENULIS BIOGRAFI SISWA KELAS X TKC.2 SMK NEGERI 4 KOTA JAMBI TAHUN AJARAN 2017/2018 - Tri Hastutik; Ade Rahima; Erlina Zahar (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2018)
This research is aimed at describing the effect of students library towards students ability in writing biography at students class X TKC.2 SMK Negeri 4 Kota Jambi Academic Year 2017/2018. This research is descriptive qualitative. The population of the research is all of students in class X SMK Negeri 4 Kota Jambi which consists of 30 students. This research uses total sampling. The data is taken from questionnaire and task. The data is analyzed by using qualitative analysis, by using statistic count. The result of the analysis is presented in a form of numbers and description. Based on the analysis, it can be seen that the result of pretest is 65,27, while the result of postest that is taught by using the benefit of school library is 77,33. It is proven with hypothesis test by using t-test which falls into 8,547 which is more higher than ttabe 2,045. It means that the use of school library has a good effect in increasing students learning outcome in writing biography where Ha is accepted. Based on the hypothesis test, the school library can be used by the teacher in giving lessons to the students especially in writing biography.Key Word: writing biography, effect of students library